Investigation into resilience of precast concrete floors against progressive collapse - Qian, Kai (2019)
The casualties and economic loss in historic events have revealed that progressive collapse performance of buildings has to be evaluated in structural design to prevent such disastrous events. Integrity and resilience are important characteristics for buildings to prevent total collapse or disproportionate collapse once an unpredictable terrorism event unfortunately occurs. Compared to the extensive studies on behavior of cast-in-place reinforced concrete (RC) buildings for progressive collapse resistance, there is less research on precast concrete (PC) buildings to mitigate progressive collapse. Thus, in this study, three one-story, two-bay largescale frame-floor subassemblies (one RC and two PC) are tested under pushdown loading regime to investigate the effect of PC floor units and transverse beams on progressive collapse resilience of PC moment-resisting frames. It is found that the PC beams and slab systems could provide substantial compressive arch action and compressive membrane action, similar to the cast-in-place RC buildings. However, as PC slabs are discontinuous, insignificant tensile membrane action is able to develop in PC slab systems and the ultimate load capacity in enormous deformation stage is mainly attributed to the catenary action developed in PC beams.